Business networks in Japan : supplier-customer interaction in product development - Laage-Hellman, Jens (Routledge advances in Asia-Pacific business, 1997)
Business Networks in Japan explores the creation of supplier-customer networks through case studies of two of Japan's largest companies: the Toshiba Corporation and the Nippon Steel Corporation.